Avaliação do efeito modulador de resistência dos alcaloides tropanos eb-pa e eb-pb em células de câncer de pulmão resistentes a quimioterápicos - Mendoza, Maria Fernanda Madrid (2024)
Multidrug resistance (MDR) is a phenomenon exhibited by lung cancer and represents a fundamental obstacle to successful treatments. Tumor cells commonly achieve the MDR phenotype through overexpression and/or increased activity of ABC transporters. The MDR1, MRP1, and MRP2 transporters are a major cause of MDR and are therefore a valuable target in reversing MDR. In this context, several generations of ABC efflux transporter inhibitors have been developed, however, most of them have failed due to serious adverse effects. Considering the above, the objective of this work was to develop an in vitro biological model resistant to cisplatin from the parental line A549 to screen resistance modulating compounds and evaluate the MDR modulating effects of isolated tropane alkaloids (EB-PA and EB-PB). of the species Erythroxylum Bezerreae in combination with cisplatin against a resistant lung cancer cell line (A549DDP20). The developed biological model A549DDP20 presents a multidrug resistance phenotype showing cross-resistance to doxorubicin and paclitaxel, overexpression of MDR1, MRP1 and MRP2 proteins, and showing changes in the cytogenetic profile after the end of resistance induction. Cisplatin, when treated alone, presented IC50 of 171.30 µM and 10.62 µM in lines A549DDP20 and A549 respectively. Furthermore, it was observed that EB-PA showed a medium resistance modulation effect after 3 and 24 hours of treatment, but EB-PB showed a low modulation effect. Thus, the combination obtained with EB-PA's CompuSym software of EB-PA and cisplatin, combination index values <1 were observed, showing a synergistic effect. There is the possibility that this potentiation of cisplatin is due, in principle, to the blockade of efflux pumps related to MDR by EB-PA. 7 different combinations were tested (DDP 10 µM+ See 10 µM, DDP 10 µM+ See 20 µM, DDP 20 µM+ See 20 µM, DDP 10 µM+ EB-PA 5 µM, DDP 10 µM+ EB-PA 10 µM, DDP 10 µM+ EB- PA 37 µM and DDP 20 µM+ EB-PA 37 µM) observing a reduction in viability, cell density, a decrease in colony formation and an increase in the pro-apoptotic protein BAX in the presence of EB-PA and cisplatin. Furthermore, it was observed that EB-PA does not affect the expression of MDR1, MRP1 and MRP2 proteins alone or in combination. Results from in silico tests showed the interaction at ATP binding sites in the MDR1 protein and in the MRP1 protein hydrophobic interactions and hydrogen bonds of EB-PA and EB-PB.